Dampak Sosial dari Kasus Perceraian yang Tidak Sah Bagi Masyarakat di Gereja Katolik - Anjeli Sarma; Floriana Doa; Herlinda Keron (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
Marriage in the Catholic Church is characterized by unity and indissolubility. This means that if a marriage in the Catholic Church is one and indissoluble, but a divorce still occurs, the divorce is considered invalid under Catholic Church law. Therefore, the researcher conducted this study to address the rampant divorce cases in society and, of course, to highlight Catholics who undergo civil divorces. Civil divorce can be legalized by the state due to several factors that cause divorce. However, on the other hand, civil divorce makes it very difficult for Catholics to remarry in the Catholic Church. Therefore, divorce itself has a significant social impact in society, for example, it becomes a topic of discussion, especially when the person files for an annulment only to remarry with another person. This case has become a hot topic that the researcher observed in the church circles. In essence, the results of this study are about a civil divorce and the desire to remarry in the Catholic Church, which becomes an obstacle to marriage that is invalid according to the Code of Canon Law. As well as the impact of civil divorce itself. This research employed qualitative methods, including literature review and guidance from Church documents (KHK), as well as participant observation during a six-month stay with the congregation at the station. The researchers also utilized previous scientific research relevant to the research topic. The study's conclusions provide information on the causes of obstacles to marriage under Catholic Church law and the impact of civil divorce on Catholics.